Community pharmacy and public health: preserving professionalism by extending the pharmacy gaze?. Issue 2 (22nd November 2020) - Atkin, Karl; Madden, Mary; Morris, Stephanie; Gough, Brendan; McCambridge, Jim
Abstract: Community pharmacy faces ongoing challenges to its economic and social standing. A concern to legitimate professional status explains the attraction of public health. Interventions currently advocated by UK State‐sponsored health care seek to reconcile the autonomous 'entrepreneurial' patient with market‐driven solutions. Engaging critically with recent Foucauldian sociological work on pharmacy as a conduit for disciplinary power, we explore how professional ambiguity is exploited to 'manage' the subjectivities of community pharmacists. Locating our discussion in the observed empirical realities of pharmacy practice (the inclusion of alcohol and other 'healthy living' advice in the Medicines Use Review), we connect unresolved historical debates in community pharmacy with current ongoing (neoliberal) changes in policy and pharmacy business practices, drawing attention to the poor evidence base underpinning healthy living activities in community pharmacy. Our findings show how community pharmacists struggle to provide meaningful advice, valued by patients. Instead of enhancing professional status, 'add‐on' public health roles created the risk of offering little more than an essentialised enactment of consumerist health care. Understanding how patients conceptualise drinking and 'healthy living' in relation to their long‐term health, using more open discussions, including the negotiation (rather than provision) of information, could help community pharmacists challenge the current professional vulnerabilities they face.